Need for Additional Glaucoma Surgery and Complications Following Glaucoma Drainage Device Surgery. Issue 6 (June 2021) - Kung, Felix F.; Knier, Catherine G.; Garmany, Armin; Mejia, Camilo A.; Sargent, Jason M.; Jamali Dogahe, Sepideh; Sabbagh, Nouran; Hodge, David O.; Khanna, Cheryl L.
Abstract : Précis: In this longitudinal study of patients with open-angle (OAG), pseudoexfoliative (PXE), or neovascular glaucoma (NVG) receiving glaucoma drainage devices (GDD), posttube cumulative rates of reoperation, corneal graft, and visually threatening complications (VT-complications) increased beyond 5 years and were not significantly affected by glaucoma type. Purpose: To study the need for additional glaucoma surgery and development of complications after first GDD surgery in eyes with primary OAG, PXE, or NVG glaucoma. Patients and Methods: There were 306 eyes with OAG (n=185), PXE (n=60), or NVG (n=61) glaucoma who received a first GDD between 1996 and 2017. Outcomes including glaucoma reoperation, corneal graft procedure, and VT-complications after GDD were measured. Kaplan-Meier analysis was used to compare cumulative rate of reaching outcomes over time after GDD placement among the 3 glaucoma groups. Results: When comparing the OAG, PXE, and NVG groups, there were no significant differences in post-GDD cumulative rates of reoperation ( P =0.33), corneal graft ( P =0.26), or VT-complications ( P =0.65) over time. For all eyes, the overall cumulative rates for each outcome measure increased beyond 5 years, and specific Kaplan-Meier rates (5-y, 10-y) included: reoperation (16%, 25%), corneal graft (6%, 12%), VT-complications (9%, 14%). When comparing specific GDDs, the Ahmed FP7 had a higher cumulative reoperation rate over time compared with the Baerveldt 350 ( P =0.019). Conclusion: Glaucoma type did not significantly affect post-GDD cumulative rates of reoperation, corneal graft, and VT-complication among the OAG, PXE, and NVG groups. For all eyes, cumulative rates of reoperation, corneal graft, and VT-complications increased beyond 5 years. The Ahmed FP7 had a significantly higher cumulative reoperation rate compared with the Baerveldt 350 over time. Abstract : Supplemental Digital Content is available in the text.